Photoluminescent SBA-16 Rhombic Dodecahedral Particles: Assembly, Characterization, and ab Initio Modeling - Ruso, Juan Manuel (2015)
Nowadays, the use of polyhedral instead of spherical particles as building blocks of engineering new materials has become an area of particular effort in the scientific community. Therefore, fabricating in a reproducible manner large amounts of uniform crystal-like particles is a huge challenge. In this work we report a low reagent-consuming BINARY surfactant templated method mediated by a hydrothermal treatment as a facile and controllable route for the synthesis of crystal-like rombdodecahedral particles exhibiting SBA-16 mesoporosity. It was determined that the hydrothermal treatment conditions were a key point upon the final material morphology, surface area, microporosity, wall thickness, and mesopore width. As a consequence of their internal mesoporosity order, rhombic dodecahedral synthesized particles exhibited highly efficient ultraviolet absorptions and photoluminescence emissions at room temperature. Conducting experimental and theoretical comparative studies allowed us to infer that the presence of intrinsic defects confined into an ordered mesoporous structure plays a very important role in semiconductor materials. The information presented here is expected to be useful, giving new, accurate information, for the construction of novel technological devices.